A modified water quality model for the Estero de Paco as a tool for remediation - Clemente, Eligia D.
As one of the tributaries of the Pasig River, the Estero de Paco was identified as a major contributor to the pollution of the Pasig River. The Estero de Paco water quality shows dependence on the type of the pollutants originating upstream or downstream based on the tide, watershed discharge and downstream river flow conditions. Despite the technologies put in place to address the concern, the water quality has not been able to reach the minimum Dissolved Oxygen (DO) level set by the DENR-EMB for Class C River (5.0 mg/L). A dissolved oxygen model is proposed to be used in aid of identifying and comparing alternatives for remediation strategies to achieve the Class C status. The Streeter-Phelps model was considered as starting point for the model since it captures the effects of both de-oxygenation and re-aeration due to the river configuration and BOD loads. For this study, the final model developed shows that 93% of the oxygen deficit comes from the Streeter Phelps component, with 3.79% from solid waste loading, 2.89% from nitrification, and the rest from photosynthesis, respiration and sediment oxygen demand. Of the 93% oxygen deficit in the Streeter Phelps component, 84% was found to be contributed by the pipe outfalls in identified areas. Through the model, the aeration component caused by the aerator and the Bio matrix filters which have been installed have been found to increase dissolved oxygen, but affected areas are limited to a perimeter of about 5 to 7 meters from the aerator. During the wet season, these reactors have been found to trap solid waste and other debris thus contributing to oxygen deficit. Based on the model simulations conducted, the following recommendations may address the oxygen deficit of the river: 1. Untreated sewage should not be discharged unto the river. 2. The operation of the island reactors in front of the Paco Market area provides additional oxygen inputs. A fixed schedule can be planned corresponding to the times when the oxygen demand is high as seen from the model. 3. Monitoring the growth of the grass and other plants in place at the constructed wetlands will prevent pollution loading from rotten leaves, waste from stray animals and rotting dead animals. Maintaining a regular dredging schedule will prevent the accumulation of sludge and other settled suspended matter particularly in the areas from President Sergio Osmena Avenue to President Quirino Avenue and from Pedro Gil Street to Gregorio Apacible Street where bed elevation shows the presence of dips in the bed. The regular removal of the collected waste below the UN Bridge area should be practiced, on a daily basis if possible, to avoid the accumulation and decay of these solid wastes. 4. Finally, the model shows that at the times when the River Warriors conduct inspection rounds and clean-ups, the river water quality drastically improves. It is thus recommended that the community engagement with stakeholders be conducted regularly to keep the river free from waste.